Real-time simulation of ultrasound refraction phenomena using ray-trace based wavefront construction method. Issue 135 (October 2016) - Szostek, Kamil; Piórkowski, Adam
Highlights: A method for real-time ultrasound simulation with refraction. The first ultrasound simulator that takes into account refraction, based on CT data. Our method is an adaptation of one of the methods known in geophysics. The method for obtaining a model of a patient body (velocity and reflection) from CT. Abstract: Ultrasound (US) imaging is one of the most popular techniques used in clinical diagnosis, mainly due to lack of adverse effects on patients and the simplicity of US equipment. However, the characteristics of the medium cause US imaging to imprecisely reconstruct examined tissues. The artifacts are the results of wave phenomena, i.e. diffraction or refraction, and should be recognized during examination to avoid misinterpretation of an US image. Currently, US training is based on teaching materials and simulators and ultrasound simulation has become an active research area in medical computer science. Many US simulators are limited by the complexity of the wave phenomena, leading to intensive sophisticated computation that makes it difficult for systems to operate in real time. To achieve the required frame rate, the vast majority of simulators reduce the problem of wave diffraction and refraction. The following paper proposes a solution for an ultrasound simulator based on methods known in geophysics. To improve simulation quality, a wavefront construction method was adapted which takes into account the refraction phenomena. This technique uses ray tracing and velocity averaging to construct wavefronts in the simulation. Instead of a geological medium, real CT scans are applied. This approach can produce more realistic projections of pathological findings and is also capable of providing real-time simulation.